Manajemen Strategi dalam Meningkatkan Daya Saing di SD Islam Cendikia Faiha Palembang - Agustin, Novia; Niswah, Choirun; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze strategic management in improving competitiveness at SD Islam Cendikia Faiha Palembang. The type of qualitative research with a descriptive approach. The informants were 4 people with purposive sampling technique, with data collection methods through interviews, observation and documentation. Data analysis techniques through data collection, presentation and verification and drawing conclusions. Data validity checking techniques through triangulation. The results and discussions state that strategic management in improving competitiveness at SD Islam Cendikia Faiha Palembang has been implemented quite well, namely by procuring facilities, improving student achievement, and carrying out various innovations in learning